The Existence and Constraint of Marriage Registration for the Followers of Sapta Darma Belief in East Lampung - Asnawi, Habib Shulton; Setiawan, Agus; Iwannudin, Iwannudin (UIN Sunan Kalijaga, 2021)
Abstract: Indonesia has provided the institution in charge of marriage registration. However, the registration process does not always run effectively for a particular community. This article sheds light on the existence and obstacle of marriage registration faced by the followers of Sapta Darma belief in East Lampung. Data were collected through observation, documentation, and interview. Using a socio-legal lens, this article identifies consecutive facts impeding followers of the Sapta Darma belief in East Lampung from obtaining the legality of their marriages through state institutions. The organization of Sapta Darma believers has no internal institution which especially in charge of registering their marriage. They seem trapped and face a disproportionately negative stigma. Many of them do not have identity cards (KTP) as the basic term for the registration process. However, they continue to believe that their marriages are valid according to their faith and do not violate state law.Abstract: Indonesia telah menyediakan lembaga yang bertanggung jawab atas pendaftaran pernikahan. Namun demikian, proses pendaftaran pernikahan tidak selalu berjalan efektif untuk komunitas tertentu. Artikel ini bertujuan untuk menjelaskan keberadaan dan hambatan pendaftaran pernikahan yang dihadapi oleh para pengikut Sapta Darma di Lampung Timur. Data dikumpulkan melalui pengamatan, dokumentasi, dan wawancara. Menggunakan lensa sosio-hukum, artikel ini mengidentifikasi fakta berturut-turut yang menghambat pengikut kepercayaan Sapta Darma di Lampung Timur untuk mendapatkan legalitas pernikahan mereka melalui lembaga negara. Organisasi Sapta Darma tidak memiliki institusi internal yang terutama bertugas mendaftarkan pernikahan mereka. Mereka tampak terjebak dan menghadapi stigma negatif yang tidak proporsional. Banyak dari mereka tidak memiliki kartu tanda penduduk (KTP) sebagai persyaratan dasar untuk pendaftaran pernikahan mereka. Namun demikian, mereka tetap percaya bahwa pernikahan mereka sah menurut keyakinan mereka dan tidak melanggar hukum negara.